β-Hydroxybutyrate Oxidation in Exercise Is Impaired by Low-Carbohydrate and High-Fat Availability - Dearlove, David J.; Holdsworth, David; Kirk, Tom; Hodson, Leanne; Charidemou, Evelina; Kvalheim, Eline; Stubbs, Brianna; Beevers, Andrew; Griffin, Julian L.; Evans, Rhys; Robertson, Jeremy; Clarke, Kieran; et al. (Frontiers in Medicine, 2021)
Abstract Purpose: Here, we determined ketone oxidation rates in athletes under metabolic conditions of high and low carbohydrate and fat availability. Methods: Six healthy male athletes completed 1 hour of bicycle ergometer exercise at 75% maximal power on three occasions. Prior to exercise, participants consumed 573 mg·kg bw-1 of a ketone ester containing a 13C label. To manipulate carbohydrate availability, 36 hours before each visit athletes undertook glycogen depleting exercise followed by isocaloric high-carbohydrate or very-low-carbohydrate diets. To manipulate fat availability, participants were given a continuous infusion of lipid during two visits. Using stable isotope methodology 𝛽-hydroxybutyrate oxidation rates were therefore investigated under the following metabolic conditions: (i) high carbohydrate + normal fat (KE+CHO); (ii) high carbohydrate + high fat (KE+CHO+FAT); and (iii) low carbohydrate + high fat (KE+FAT). Results: Pre-exercise intramuscular glycogen was approximately halved in the KE+FAT vs. KE+CHO and KE+CHO+FAT conditions (both p<0.05). Blood free fatty acids and intramuscular long-chain acylcarnitines were significantly greater in the KE+FAT vs. other conditions and in the KE+CHO+FAT vs. KE+CHO conditions before exercise. Following ingestion of the 13C labelled ketone ester, blood 𝛽-hydroxybutyrate levels increased to ≈4.5 mM before exercise in all conditions. 𝛽-hydroxybutyrate oxidation was modestly greater in the KE+CHO vs. KE+FAT conditions (mean diff. = 0.09 g·min-1; p=0.03; d=0.3), tended to be greater in the KE+CHO+FAT vs. KE+FAT conditions (mean diff. = 0.07 g·min-1; p=0.1; d=0.3) and were the same in the KE+CHO+FAT vs. KE+FAT conditions (p<0.05; d<0.1). A moderate positive correlation between pre-exercise intramuscular glycogen and 𝛽-hydroxybutyrate oxidation rates during exercise was present (p=0.04; r=0.5). Post-exercise intramuscular 𝛽-hydroxybutyrate abundance was elevated in the vs. KE+CHO and KE+CHO+FAT conditions (both, p<0.001; d=2.3). Conclusion: 𝛽-hydroxybutyrate oxidation rates during exercise are modestly impaired by low carbohydrate availability, independent of circulating 𝛽-hydroxybutyrate levels.